2015
DOI: 10.1016/j.radi.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A 6-year study of mammographic compression force: Practitioner variability within and between screening sites

Abstract: The application of compression force in mammography is more heavily influenced by the practitioner rather than the client. This can affect client experience, radiation dose and image quality. This research investigates practitioner compression force variation over a six year screening cycle in three different screening units

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 10 publications
6
47
0
Order By: Relevance
“…Both guidelines accept a large range of compression forces and this might be one of the reasons for the observed variation in compression forces in this study and Mercer et al's [8][9][10] from the UK.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Both guidelines accept a large range of compression forces and this might be one of the reasons for the observed variation in compression forces in this study and Mercer et al's [8][9][10] from the UK.…”
Section: Discussionmentioning
confidence: 48%
“…[8][9][10][11]22,23 Factors related to the screened female include differences in breast volume, 18 breast stiffness and compressibility 19,20 and acceptance of pain. Characteristics of the breast compression paddle, 24 positioning of the compression paddle, 22,23 positioning of the detector plate 21 and use of automated compression force methods 22 are factors related to the equipment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous quantitative research into the application of breast compression has shown that intra and inter practitioner variability does exist within and between centres, [9][10][11] and our research highlights complex assumptions that may lead to individual practitioners prioritising decision making factors differently. The practitioner ranks the different priorities in the decision process, which could be considered to be a form of Analytical Hierarchical Processing.…”
mentioning
confidence: 73%